NVQ engineering mandatory units - Salmon, David (Longman NVQ, 1997)
Aimed at both the trainee and training provider, this workbook offers a programme of development of the practical knowledge required for the five mandatory units of the Engineering Manufacture (Foundation) course at NVQ Level 2.